A corrosion-resistant stainless steel casting for ships and its preparation process
By performing composite laser cladding such as nickel-based alloy powder and ternary co-permeable treatment of stainless steel castings, the problems of insufficient wear resistance, surface hardness and corrosion resistance in ship applications are solved, and higher comprehensive performance is achieved.
Patent Information
- Application Number
- CN202411346941.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Existing stainless steel castings are difficult to meet the needs of high wear resistance, surface hardness and corrosion resistance in marine applications.
Laser cladding powder is used to combine nickel-based alloy powder, cerium oxide-tungsten carbide core-shell powder and tungsten carbide powder to laser cladding the stainless steel substrate, and then nitrogen, carbon and oxygen ternary co-permeation is carried out.
It significantly improves the wear resistance, surface hardness and corrosion resistance of stainless steel castings, and improves its practicality in marine applications.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel, in particular to a corrosion-resistant stainless steel casting for ships and a preparation process thereof. Background Art
[0002] Since the advent of stainless steel in the early twentieth century, stainless steel has been widely used in various fields of life, such as industrial machinery and equipment, aerospace castings, and ship castings, due to its advantages such as good corrosion resistance, high processing performance and low cost. Therefore, R&D personnel have high requirements for the surface hardness, wear resistance and corrosion resistance of stainless steel castings, especially for stainless steel castings used in ships, whose corrosion resistance is one of our key concerns.
[0003] In the existing research and development process, in order to improve the comprehensive performance of stainless steel castings, they are generally subjected to surface modification treatments such as vacuum sputtering, laser cladding, paint coating, etc. Ion nitriding is also one of the more common modification methods. Based on this, the present application discloses a corrosion-resistant stainless steel casting for ships and a preparation process thereof, so as to provide a stainless steel casting with excellent corrosion resistance. Summary of the invention
[0004] The object of the present invention is to provide a corrosion-resistant stainless steel casting for ships and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A preparation process of a corrosion-resistant stainless steel casting for a ship, comprising the following steps:
[0007] Step 1: Grind the stainless steel substrate, clean it with acetone ultrasonic for 20-30 minutes, and then rinse it with deionized water and dry it;
[0008] The nickel-based alloy powder, cerium oxide-tungsten carbide core-shell powder and tungsten carbide powder are mixed, mechanically ground for 20-30 minutes, and dried at 80-85°C for 1-1.5 hours to obtain cladding powder; the cladding powder and the binder are evenly stirred, pre-placed on the surface of the stainless steel substrate to form a pre-placed powder layer, dried at 80-85°C for 3-4 hours, and then laser cladding is performed to obtain pre-treated stainless steel;
[0009] Step 2: Take the pretreated stainless steel, clean it with acetone, transfer it to a plasma nitriding furnace, evacuate it to a pressure of 5-6 Pa, introduce hydrogen with a hydrogen flow rate of 0.5-0.6 L / min, sputter clean the surface for 20-30 minutes, and then perform nitrogen-carbon co-diffusion after sputter cleaning to obtain corrosion-resistant stainless steel.
[0010] In a more optimized solution, in step 1, the amount of tungsten carbide powder in the cladding powder is 30-40wt%, and the amount of cerium oxide-tungsten carbide core-shell powder is 1-3wt% by mass fraction; the binder is water glass, and the thickness of the preset powder layer is 1.5-2mm.
[0011] In the more optimized solution, in step 1, the laser cladding process is as follows: the overlap rate is 40%, the scanning speed is 5-6 mm / s, the protective gas is argon, the flow rate is 10-12 L / min, the spot diameter is 3 mm, and the laser power is 1000-1200 W.
[0012] In the more optimized scheme, in step 2, the specific steps of nitrocarburizing are as follows: after sputtering cleaning, nitrogen and methane are introduced, wherein the nitrogen concentration is 98.5%, and the methane concentration is 1.5%, the pressure in the furnace is maintained at 300 Pa, the temperature is raised to 500-510°C, air is introduced, the air flow rate is 0.3-0.5 L / min, and the nitrocarburizing is performed for 3-4 hours.
[0013] The most optimized solution is to prepare the cerium oxide-tungsten carbide core-shell powder in the following steps:
[0014] Step S1: respectively mixing cerium nitrate hexahydrate, hexamethylenetetramine and deionized water, and stirring evenly to obtain cerium nitrate hexahydrate solution and hexamethylenetetramine solution;
[0015] Step S2: tungsten carbide and anhydrous ethanol are mixed, ultrasonically dispersed for 20-30 minutes, cerium nitrate hexahydrate solution and hexamethylenetetramine solution are added, stirred and reacted at 75-80° C. for 2-3 hours, centrifuged after the reaction is completed, washed and dried, and calcined at 650-680° C. for 2-3 hours to obtain cerium oxide-tungsten carbide core-shell powder.
[0016] According to a more optimized solution, in step S1, the mass fraction of the cerium nitrate hexahydrate solution is 1-2 wt %, and the mass fraction of the hexamethylenetetramine solution is 2-3 wt %.
[0017] In a more optimized solution, in step S2, the mass ratio of tungsten carbide, cerium nitrate hexahydrate, and hexamethylenetetramine is 1: (3-3.5): (4.5-5); and the stirring speed is 350-400 r / min.
[0018] In a more optimized solution, the chemical composition of the nickel-based alloy powder is as follows: by mass fraction, C: 0.80~0.90wt%, Cr: 15~15.5wt%, Si: 3.5~4wt%, Fe: 15wt%, B: 3~3.5wt%, Ti: 0.2~0.3wt%, and the remainder is Ni.
[0019] A more optimized solution is a corrosion-resistant stainless steel casting for ships prepared according to any of the preparation processes described above.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] The invention discloses a corrosion-resistant stainless steel casting for ships and a preparation process thereof. The scheme uses a stainless steel substrate as a matrix, and laser cladding is performed after the surface is cleaned, wherein the laser cladding powder is composed of a composite of nickel-based alloy powder, cerium oxide-tungsten carbide core-shell powder, and tungsten carbide powder. After laser cladding, nitrogen, carbon, and oxygen ternary co-penetration is performed. The prepared stainless steel casting not only has excellent wear resistance, but also has improved surface hardness, improved corrosion resistance, and greatly improved practicability.
[0022] When the stainless steel substrate is conventionally surface nitrided, the nitriding speed is slow and the nitriding layer is shallow. The surface brittleness of the stainless steel casting is high, and the corrosion resistance cannot meet the actual needs. Therefore, rare earth elements are generally used to catalyze the nitriding process, but the improvement effect is not obvious and the actual effect is poor. Therefore, this scheme first performs laser cladding on the stainless steel substrate, and forms a cladding powder by compounding nickel-based alloy powder, cerium oxide-tungsten carbide core-shell powder, and tungsten carbide powder. The addition of tungsten carbide powder can effectively improve the surface hardness and wear resistance of the stainless steel casting. The addition of cerium oxide-tungsten carbide core-shell powder can not only improve the wear resistance and corrosion resistance of the laser cladding layer itself, thereby improving the comprehensive performance of the stainless steel casting, but also the introduction of cerium oxide-tungsten carbide core-shell powder can promote the thickness of the subsequent ion ternary co-diffusion layer and improve the ion ternary co-diffusion treatment effect.
[0023] It should be noted that in this scheme, it is specifically defined that "the amount of tungsten carbide powder in the cladding powder is 30~40wt%, and the amount of cerium oxide-tungsten carbide core-shell powder is 1~3wt%". Under this parameter dosage, the performance of the stainless steel casting obtained is the best; at the same time, compared with the scheme of only introducing cerium oxide in the laser cladding layer, the effect of this scheme is obviously inferior to that of this application.
[0024] On this basis, this scheme carried out nitrogen, carbon and oxygen ternary co-diffusion, specifically "the specific steps of nitrogen and carbon co-diffusion are: after sputtering cleaning, nitrogen and methane are introduced, wherein the nitrogen concentration is 98.5%, and the methane concentration is 1.5%, the gas pressure in the furnace is maintained at 300Pa, the temperature is raised to 500~510℃, air is introduced, the air flow rate is 0.3~0.5L / min, and the co-diffusion is carried out for 3~4h". Due to the presence of the laser cladding layer, compared with the direct nitrogen, carbon and oxygen ternary co-diffusion on the surface of the stainless steel substrate, the wear resistance, hardness and corrosion resistance of the product obtained by this scheme are better. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In this embodiment, the stainless steel substrate is 45 steel, and the specific chemical composition is: 0.46wt% C, 0.17wt% Si, 0.52wt% Mn, 0.031wt% S, 0.032wt% P, and the rest is Fe. The particle size of tungsten carbide is 200 mesh.
[0027] Embodiment 1: A process for preparing a corrosion-resistant stainless steel casting for a ship, comprising the following steps:
[0028] Step 1: Grind the stainless steel substrate, ultrasonically clean it with acetone for 20 minutes, and then rinse it with deionized water and dry it.
[0029] Nickel-based alloy powder, cerium oxide-tungsten carbide core-shell powder, and tungsten carbide powder were mixed, mechanically ground for 30 minutes, and dried at 80°C for 1.5 hours to obtain cladding powder; the chemical composition of the nickel-based alloy powder is as follows: by mass fraction, C: 0.80wt%, Cr: 15.5wt%, Si: 4wt%, Fe: 15wt%, B: 3.5wt%, Ti: 0.2wt%, and the remainder is Ni. By mass fraction, the amount of tungsten carbide powder in the cladding powder is 40wt%, and the amount of cerium oxide-tungsten carbide core-shell powder is 1wt%; the binder is water glass, and the thickness of the preset powder layer is 1.5mm.
[0030] The cladding powder and binder are mixed evenly, pre-placed on the surface of the stainless steel substrate to form a pre-placed powder layer, dried at 80°C for 4 hours, and then laser cladding is performed to obtain pre-treated stainless steel. The laser cladding process is as follows: the overlap rate is 40%, the scanning speed is 5mm / s, the protective gas is argon, the flow rate is 10L / min, the spot diameter is 3mm, and the laser power is 1200W.
[0031] The preparation steps of cerium oxide-tungsten carbide core-shell powder are as follows:
[0032] Step S1: respectively mixing cerium nitrate hexahydrate, hexamethylenetetramine and deionized water, and stirring evenly to obtain a cerium nitrate hexahydrate solution and a hexamethylenetetramine solution; the mass fraction of the cerium nitrate hexahydrate solution is 1.5wt%, and the mass fraction of the hexamethylenetetramine solution is 2.5wt%.
[0033] Step S2: 0.1 g of tungsten carbide and anhydrous ethanol are mixed, ultrasonically dispersed for 20 minutes, cerium nitrate hexahydrate solution and hexamethylenetetramine solution are added, stirred and reacted at 75°C for 3 hours, centrifuged after the reaction is completed, washed and dried, and calcined at 650°C for 3 hours to obtain cerium oxide-tungsten carbide core-shell powder. The mass ratio of tungsten carbide, cerium nitrate hexahydrate, and hexamethylenetetramine is 1:3.2:4.8; the stirring speed is 350r / min.
[0034] Step 2: Take the pretreated stainless steel, clean it with acetone, transfer it to a plasma nitriding furnace, evacuate it to a pressure of 5 Pa, introduce hydrogen with a hydrogen flow rate of 0.5 L / min, sputter clean the surface for 30 minutes, and then perform nitrogen and carbon co-diffusion after sputter cleaning to obtain corrosion-resistant stainless steel.
[0035] The specific steps of nitrocarburizing are as follows: after sputtering cleaning, nitrogen and methane are introduced, wherein the nitrogen concentration is 98.5% and the methane concentration is 1.5%, the pressure in the furnace is maintained at 300Pa, the temperature is raised to 510°C, air is introduced, the air flow rate is 0.3L / min, and the nitrocarburizing is performed for 4 hours.
[0036] Embodiment 2: A process for preparing a corrosion-resistant stainless steel casting for a ship, comprising the following steps:
[0037] Step 1: Grind the stainless steel substrate, ultrasonically clean it with acetone for 25 minutes, and then rinse it with deionized water and dry it.
[0038] Nickel-based alloy powder, cerium oxide-tungsten carbide core-shell powder, and tungsten carbide powder were mixed, mechanically ground for 30 minutes, and dried at 85°C for 1.5 hours to obtain cladding powder; the chemical composition of the nickel-based alloy powder is as follows: by mass fraction, C: 0.80wt%, Cr: 15.5wt%, Si: 4wt%, Fe: 15wt%, B: 3.5wt%, Ti: 0.2wt%, and the remainder is Ni. By mass fraction, the amount of tungsten carbide powder in the cladding powder is 39wt%, and the amount of cerium oxide-tungsten carbide core-shell powder is 2wt%; the binder is water glass, and the thickness of the preset powder layer is 1.5mm.
[0039] The cladding powder and binder were mixed evenly, pre-placed on the surface of the stainless steel substrate to form a pre-placed powder layer, dried at 85°C for 3.5 hours, and then laser cladding was performed to obtain pre-treated stainless steel. The laser cladding process is as follows: the overlap rate is 40%, the scanning speed is 5mm / s, the protective gas is argon, the flow rate is 10L / min, the spot diameter is 3mm, and the laser power is 1200W.
[0040] The preparation steps of cerium oxide-tungsten carbide core-shell powder are as follows:
[0041] Step S1: respectively mixing cerium nitrate hexahydrate, hexamethylenetetramine and deionized water, and stirring evenly to obtain a cerium nitrate hexahydrate solution and a hexamethylenetetramine solution; the mass fraction of the cerium nitrate hexahydrate solution is 1.5wt%, and the mass fraction of the hexamethylenetetramine solution is 2.5wt%.
[0042] Step S2: 0.1 g of tungsten carbide and anhydrous ethanol are mixed, ultrasonically dispersed for 25 minutes, cerium nitrate hexahydrate solution and hexamethylenetetramine solution are added, stirred and reacted at 80°C for 2.5 hours, centrifuged after the reaction is completed, washed and dried, and calcined at 650°C for 3 hours to obtain cerium oxide-tungsten carbide core-shell powder. The mass ratio of tungsten carbide, cerium nitrate hexahydrate, and hexamethylenetetramine is 1:3.2:4.8; the stirring speed is 350r / min.
[0043] Step 2: Take the pretreated stainless steel, clean it with acetone, transfer it to a plasma nitriding furnace, evacuate it to a pressure of 5 Pa, introduce hydrogen with a hydrogen flow rate of 0.5 L / min, sputter clean the surface for 30 minutes, and then perform nitrogen and carbon co-diffusion after sputter cleaning to obtain corrosion-resistant stainless steel.
[0044] The specific steps of nitrocarburizing are as follows: after sputtering cleaning, nitrogen and methane are introduced, wherein the nitrogen concentration is 98.5% and the methane concentration is 1.5%, the pressure in the furnace is maintained at 300Pa, the temperature is raised to 510°C, air is introduced, the air flow rate is 0.3L / min, and the nitrocarburizing is performed for 4 hours.
[0045] Embodiment 3: A process for preparing a corrosion-resistant stainless steel casting for a ship, comprising the following steps:
[0046] Step 1: Grind the stainless steel substrate, ultrasonically clean it with acetone for 30 minutes, and then rinse it with deionized water and dry it.
[0047] Nickel-based alloy powder, cerium oxide-tungsten carbide core-shell powder, and tungsten carbide powder were mixed, mechanically ground for 30 minutes, and dried at 85°C for 1 hour to obtain cladding powder; the chemical composition of the nickel-based alloy powder is as follows: by mass fraction, C: 0.80wt%, Cr: 15.5wt%, Si: 4wt%, Fe: 15wt%, B: 3.5wt%, Ti: 0.2wt%, and the remainder is Ni. By mass fraction, the amount of tungsten carbide powder in the cladding powder is 38wt%, and the amount of cerium oxide-tungsten carbide core-shell powder is 3wt%; the binder is water glass, and the thickness of the preset powder layer is 1.5mm.
[0048] The cladding powder and binder were mixed evenly, pre-placed on the surface of the stainless steel substrate to form a pre-placed powder layer, dried at 85°C for 3h, and then laser cladding was performed to obtain pre-treated stainless steel. The laser cladding process is as follows: the overlap rate is 40%, the scanning speed is 5mm / s, the protective gas is argon, the flow rate is 10L / min, the spot diameter is 3mm, and the laser power is 1200W.
[0049] The preparation steps of cerium oxide-tungsten carbide core-shell powder are as follows:
[0050] Step S1: respectively mixing cerium nitrate hexahydrate, hexamethylenetetramine and deionized water, and stirring evenly to obtain a cerium nitrate hexahydrate solution and a hexamethylenetetramine solution; the mass fraction of the cerium nitrate hexahydrate solution is 1.5wt%, and the mass fraction of the hexamethylenetetramine solution is 2.5wt%.
[0051] Step S2: 0.1 g of tungsten carbide and anhydrous ethanol are mixed, ultrasonically dispersed for 30 minutes, cerium nitrate hexahydrate solution and hexamethylenetetramine solution are added, stirred and reacted at 80°C for 2 hours, centrifuged after the reaction is completed, washed and dried, and calcined at 650°C for 3 hours to obtain cerium oxide-tungsten carbide core-shell powder. The mass ratio of tungsten carbide, cerium nitrate hexahydrate, and hexamethylenetetramine is 1:3.2:4.8; the stirring speed is 350r / min.
[0052] Step 2: Take the pretreated stainless steel, clean it with acetone, transfer it to a plasma nitriding furnace, evacuate it to a pressure of 5 Pa, introduce hydrogen with a hydrogen flow rate of 0.5 L / min, sputter clean the surface for 30 minutes, and then perform nitrogen and carbon co-diffusion after sputter cleaning to obtain corrosion-resistant stainless steel.
[0053] The specific steps of nitrocarburizing are as follows: after sputtering cleaning, nitrogen and methane are introduced, wherein the nitrogen concentration is 98.5% and the methane concentration is 1.5%, the pressure in the furnace is maintained at 300Pa, the temperature is raised to 510°C, air is introduced, the air flow rate is 0.3L / min, and the nitrocarburizing is performed for 4 hours.
[0054] Comparative Example 1: Using Example 3 as a control, in Comparative Example 1, cerium oxide-tungsten carbide core-shell powder was not added, and the other steps remained unchanged.
[0055] A preparation process of a corrosion-resistant stainless steel casting for a ship, comprising the following steps:
[0056] Step 1: Grind the stainless steel substrate, ultrasonically clean it with acetone for 30 minutes, and then rinse it with deionized water and dry it.
[0057] Nickel-based alloy powder and tungsten carbide powder were mixed, mechanically ground for 30 minutes, and dried at 85°C for 1 hour to obtain cladding powder; the chemical composition of the nickel-based alloy powder was as follows: by mass fraction, C: 0.80wt%, Cr: 15.5wt%, Si: 4wt%, Fe: 15wt%, B: 3.5wt%, Ti: 0.2wt%, and the remainder was Ni. By mass fraction, the amount of tungsten carbide powder in the cladding powder was 41wt%; the binder was water glass, and the thickness of the preset powder layer was 1.5mm.
[0058] The cladding powder and binder were mixed evenly, pre-placed on the surface of the stainless steel substrate to form a pre-placed powder layer, dried at 85°C for 3h, and then laser cladding was performed to obtain pre-treated stainless steel. The laser cladding process is as follows: the overlap rate is 40%, the scanning speed is 5mm / s, the protective gas is argon, the flow rate is 10L / min, the spot diameter is 3mm, and the laser power is 1200W.
[0059] Step 2: Take the pretreated stainless steel, clean it with acetone, transfer it to a plasma nitriding furnace, evacuate it to a pressure of 5 Pa, introduce hydrogen with a hydrogen flow rate of 0.5 L / min, sputter clean the surface for 30 minutes, and then perform nitrogen and carbon co-diffusion after sputter cleaning to obtain corrosion-resistant stainless steel.
[0060] The specific steps of nitrocarburizing are as follows: after sputtering cleaning, nitrogen and methane are introduced, wherein the nitrogen concentration is 98.5% and the methane concentration is 1.5%, the pressure in the furnace is maintained at 300Pa, the temperature is raised to 510°C, air is introduced, the air flow rate is 0.3L / min, and the nitrocarburizing is performed for 4 hours.
[0061] Comparative Example 2: Taking Example 3 as a control, cerium oxide powder was added to Comparative Example 2, and the amount of cerium oxide powder was 1 wt %, and the other steps remained unchanged.
[0062] A preparation process of a corrosion-resistant stainless steel casting for a ship, comprising the following steps:
[0063] Step 1: Grind the stainless steel substrate, ultrasonically clean it with acetone for 30 minutes, and then rinse it with deionized water and dry it.
[0064] Nickel-based alloy powder, cerium oxide powder and tungsten carbide powder were mixed, mechanically ground for 30 minutes, and dried at 85°C for 1 hour to obtain cladding powder; the chemical composition of the nickel-based alloy powder is as follows: by mass fraction, C: 0.80wt%, Cr: 15.5wt%, Si: 4wt%, Fe: 15wt%, B: 3.5wt%, Ti: 0.2wt%, and the remainder is Ni. By mass fraction, the amount of tungsten carbide powder in the cladding powder is 38wt%, and the amount of cerium oxide powder is 1wt%; the binder is water glass, and the thickness of the preset powder layer is 1.5mm.
[0065] The cladding powder and binder were mixed evenly, pre-placed on the surface of the stainless steel substrate to form a pre-placed powder layer, dried at 85°C for 3h, and then laser cladding was performed to obtain pre-treated stainless steel. The laser cladding process is as follows: the overlap rate is 40%, the scanning speed is 5mm / s, the protective gas is argon, the flow rate is 10L / min, the spot diameter is 3mm, and the laser power is 1200W.
[0066] Step 2: Take the pretreated stainless steel, clean it with acetone, transfer it to a plasma nitriding furnace, evacuate it to a pressure of 5 Pa, introduce hydrogen with a hydrogen flow rate of 0.5 L / min, sputter clean the surface for 30 minutes, and then perform nitrogen and carbon co-diffusion after sputter cleaning to obtain corrosion-resistant stainless steel.
[0067] The specific steps of nitrocarburizing are as follows: after sputtering cleaning, nitrogen and methane are introduced, wherein the nitrogen concentration is 98.5% and the methane concentration is 1.5%, the pressure in the furnace is maintained at 300Pa, the temperature is raised to 510°C, air is introduced, the air flow rate is 0.3L / min, and the nitrocarburizing is performed for 4 hours.
[0068] Comparative Example 3: Taking Example 3 as a control, cerium oxide powder was added to Comparative Example 3, and the amount of cerium oxide powder was 3 wt %, and the other steps remained unchanged.
[0069] A preparation process of a corrosion-resistant stainless steel casting for a ship, comprising the following steps:
[0070] Step 1: Grind the stainless steel substrate, ultrasonically clean it with acetone for 30 minutes, and then rinse it with deionized water and dry it.
[0071] Nickel-based alloy powder, cerium oxide powder and tungsten carbide powder were mixed, mechanically ground for 30 minutes, and dried at 85°C for 1 hour to obtain cladding powder; the chemical composition of the nickel-based alloy powder is as follows: by mass fraction, C: 0.80wt%, Cr: 15.5wt%, Si: 4wt%, Fe: 15wt%, B: 3.5wt%, Ti: 0.2wt%, and the remainder is Ni. By mass fraction, the amount of tungsten carbide powder in the cladding powder is 38wt%, and the amount of cerium oxide powder is 3wt%; the binder is water glass, and the thickness of the preset powder layer is 1.5mm.
[0072] The cladding powder and binder were mixed evenly, pre-placed on the surface of the stainless steel substrate to form a pre-placed powder layer, dried at 85°C for 3h, and then laser cladding was performed to obtain pre-treated stainless steel. The laser cladding process is as follows: the overlap rate is 40%, the scanning speed is 5mm / s, the protective gas is argon, the flow rate is 10L / min, the spot diameter is 3mm, and the laser power is 1200W.
[0073] Step 2: Take the pretreated stainless steel, clean it with acetone, transfer it to a plasma nitriding furnace, evacuate it to a pressure of 5 Pa, introduce hydrogen with a hydrogen flow rate of 0.5 L / min, sputter clean the surface for 30 minutes, and then perform nitrogen and carbon co-diffusion after sputter cleaning to obtain corrosion-resistant stainless steel.
[0074] The specific steps of nitrocarburizing are as follows: after sputtering cleaning, nitrogen and methane are introduced, wherein the nitrogen concentration is 98.5% and the methane concentration is 1.5%, the pressure in the furnace is maintained at 300Pa, the temperature is raised to 510°C, air is introduced, the air flow rate is 0.3L / min, and the nitrocarburizing is performed for 4 hours.
[0075] Comparative Example 4: Taking Example 3 as a control, laser cladding was not performed in Comparative Example 4, and the other steps remained unchanged.
[0076] A preparation process of a corrosion-resistant stainless steel casting for a ship, comprising the following steps:
[0077] Step 1: Grind the stainless steel substrate, ultrasonically clean it with acetone for 30 minutes, and then rinse it with deionized water and dry it.
[0078] Step 2: Take the dried stainless steel, clean it with acetone, transfer it to a plasma nitriding furnace, evacuate it to a pressure of 5 Pa, introduce hydrogen with a hydrogen flow rate of 0.5 L / min, sputter clean the surface for 30 minutes, and then perform nitrogen and carbon co-diffusion after sputter cleaning to obtain corrosion-resistant stainless steel.
[0079] The specific steps of nitrocarburizing are as follows: after sputtering cleaning, nitrogen and methane are introduced, wherein the nitrogen concentration is 98.5% and the methane concentration is 1.5%, the pressure in the furnace is maintained at 300Pa, the temperature is raised to 510°C, air is introduced, the air flow rate is 0.3L / min, and the nitrocarburizing is performed for 4 hours.
[0080] Detection experiment:
[0081] According to the methods disclosed in Examples 1 to 3 and Comparative Examples 1 to 4, corrosion-resistant stainless steel samples were prepared, and the surface microhardness of the corrosion-resistant stainless steel samples was tested, with a load of 500 g and a holding time of 10 s; the surface wear resistance of the corrosion-resistant stainless steel samples was tested, and GCr15 was selected as the grinding material during the test, with a diameter of 5 mm, a rotation speed of 500 r / min, a loading load of 300 g, and a grinding time of 60 min. After the grinding was completed, the weight loss before and after the wear was calculated; the corrosion resistance of the corrosion-resistant stainless steel samples was tested, and a CHI604E electrochemical workstation was used during the test, the corrosive medium was 3.5 wt% NaCl, the test temperature was 25 ° C, the auxiliary electrode was a platinum electrode, the reference electrode was a saturated calomel electrode, and the sample was a working electrode to calculate the corrosion current density. Specific data are shown in Table 1.
[0082] Table 1
[0083]
[0084] Conclusion: This scheme uses stainless steel substrate as the matrix, and laser cladding is performed after surface cleaning. The laser cladding powder is composed of a composite of nickel-based alloy powder, cerium oxide-tungsten carbide core-shell powder, and tungsten carbide powder. After laser cladding, nitrogen, carbon and oxygen ternary co-penetration is performed. The prepared stainless steel casting has excellent wear resistance, improved surface hardness, and improved corrosion resistance.
[0085] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A process for preparing corrosion-resistant stainless steel castings for ships, characterized in that: The following steps are involved: Step 1: Grind the stainless steel substrate, clean it with acetone ultrasonic for 20 to 30 minutes, and then rinse it with deionized water and dry it; The nickel-based alloy powder, cerium oxide-tungsten carbide core-shell powder and tungsten carbide powder are mixed, mechanically ground for 20 to 30 minutes, and dried at 80 to 85° C. for 1 to 1.5 hours to obtain cladding powder; the cladding powder and the binder are evenly stirred, pre-placed on the surface of the stainless steel substrate to form a pre-placed powder layer, dried at 80 to 85° C. for 3 to 4 hours, and then laser cladding is performed to obtain pre-treated stainless steel; Step 2: Take the pretreated stainless steel, clean it with acetone, transfer it to a plasma nitriding furnace, evacuate it to a pressure of 5-6 Pa, introduce hydrogen, and the hydrogen flow rate is 0.5-0.6 L / min. Sputter clean the surface for 20-30 minutes, and then perform nitrocarburizing after sputter cleaning to obtain corrosion-resistant stainless steel; In step 1, the amount of tungsten carbide powder in the cladding powder is 30-40wt%, and the amount of cerium oxide-tungsten carbide core-shell powder is 1-3wt% by mass fraction; the binder is water glass, and the thickness of the preset powder layer is 1.5-2mm.
2. The process for preparing a corrosion-resistant stainless steel casting for ships according to claim 1, characterized in that: In step 1, the laser cladding process is specifically as follows: the overlap rate is 40%, the scanning speed is 5-6 mm / s, the protective gas is argon, the flow rate is 10-12 L / min, the spot diameter is 3 mm, and the laser power is 1000-1200 W.
3. The process for preparing a corrosion-resistant stainless steel casting for ships according to claim 1, characterized in that: In step 2, the specific steps of nitrogen and carbon co-diffusion are as follows: after sputtering cleaning, nitrogen and methane are introduced, wherein the nitrogen concentration is 98.5%, and the methane concentration is 1.5%, the gas pressure in the furnace is maintained at 300Pa, the temperature is raised to 500-510°C, air is introduced, the air flow rate is 0.3-0.5L / min, and the co-diffusion is carried out for 3-4h.
4. The process for preparing a corrosion-resistant stainless steel casting for ships according to claim 1, characterized in that: The preparation steps of cerium oxide-tungsten carbide core-shell powder are as follows: Step S1: respectively mixing cerium nitrate hexahydrate, hexamethylenetetramine and deionized water, and stirring evenly to obtain cerium nitrate hexahydrate solution and hexamethylenetetramine solution; Step S2: tungsten carbide and anhydrous ethanol are mixed, ultrasonically dispersed for 20 to 30 minutes, cerium nitrate hexahydrate solution and hexamethylenetetramine solution are added, stirred and reacted at 75 to 80° C. for 2 to 3 hours, centrifuged after the reaction is completed, washed and dried, and calcined at 650 to 680° C. for 2 to 3 hours to obtain cerium oxide-tungsten carbide core-shell powder.
5. The process for preparing a corrosion-resistant stainless steel casting for ships according to claim 4, characterized in that: In step S1, the mass fraction of the cerium nitrate hexahydrate solution is 1-2 wt%, and the mass fraction of the hexamethylenetetramine solution is 2-3 wt%.
6. The process for preparing a corrosion-resistant stainless steel casting for ships according to claim 4, characterized in that: In step S2, the mass ratio of tungsten carbide, cerium nitrate hexahydrate and hexamethylenetetramine is 1:(3-3.5):(4.5-5); and the stirring speed is 350-400 r / min.
7. The process for preparing a corrosion-resistant stainless steel casting for ships according to claim 1, characterized in that: The chemical composition of the nickel-based alloy powder is specifically as follows: by mass fraction, C: 0.80-0.90wt%, Cr: 15-15.5wt%, Si: 3.5-4wt%, Fe: 15wt%, B: 3-3.5wt%, Ti: 0.2-0.3wt%, and the balance is Ni.
8. A corrosion-resistant stainless steel casting for ships prepared by the preparation process according to any one of claims 1 to 7.
Citation Information
Patent Citations
Laser clad pot roll sleeves for galvanizing baths
CA2254700A1
Anti-corrosion wear-resisting coating and coating method thereof
CN103882324A